The importance of loss of control while eating in adolescents with purging disorder. Issue 8 (10th March 2016) - Goldschmidt, Andrea B.; Accurso, Erin C.; O'Brien, Setareh; Kara Fitzpatrick, Kathleen; Lock, James D.; Le Grange, Daniel
ABSTRACT: Objective: Although many individuals with purging disorder (PD) report loss of control (LOC) eating, it is unclear whether they differ from those who do not, or from other eating disorders involving purging and/or LOC. Method: We compared PD with LOC (PD‐LOC), PD without LOC (PD‐noLOC), bulimia nervosa (BN), and anorexia nervosa‐binge/purge subtype (AN‐B/P) on measures of eating‐related and general psychopathology in treatment‐seeking adolescents. Results: PD‐LOC comprised ∼30% of PD diagnoses. PD‐LOC and PD‐noLOC did not differ from one another, or from BN and AN‐B/P, on most measures of psychopathology, with some exceptions. PD‐noLOC was similar to AN‐B/P ( p  = 0.99) and significantly different from BN on eating concerns ( p  < 0.001), while PD‐LOC was similar to BN, AN‐B/P, and PD‐noLOC on this measure ( p s ≥ 0.06). PD‐LOC reported higher self‐esteem than BN, AN‐B/P, and PD‐noLOC ( p s < 0.001). Discussion: PD was largely similar to other eating disorders characterized by purging, regardless of whether LOC eating was present. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:801–804)